Successful hypnotherapy for chronic stress and headache in a middle age man - Khairi, Che Mat; Rohayah, Husain (2015)
This is a case report of a middle age man, presented with stress and headache for one year. The symptoms started following an episode of viral infection with minor fully recovered cerebral vascular accident in which he was unconscious for two weeks and managed in special ward. He also experienced frequent nightmares, difficulty sleeping, anger which so distressing for him. He has the background difficulty of raising his child with chronic mental difficulties. He completed seven therapy sessions. The goals of therapy formulated; he undergone the stabilization, change and maintenance phase of therapy. Among techniques used were relaxation, self-hypnosis, healing white light, ego strengthening, anchoring positive emotion and pseudo-orientation in time. His subjective unit of distress (SUD) scores improved from 8 to 3 out of 10. Finally he was able to understand his problems, manage his stress, control his anger and have a better quality of life